Meanings of the preposition “of” in the oral interlanguage of A2 and B2 Brazilian learners - Rocha, João Victor Pessoa (Revista X, 2022)
Prepositions are challenging for non-native speakers because of the idiosyncratic behavior of such words which do not follow any predictable pattern in similar contexts (FELICE; PULMAN, 2008). In addition, prepositions are difficult to acquire because their usage is influenced by the speakers’ mother tongue (L1) (KOOSHA & JAFARPOUR, 2006; COWAN et al., 2003; TANIMURA et al., 2004). In order to verify how non-native English speakers use prepositions, this study aims to describe how prepositional profiling of the word “of” are represented in the spoken interlanguage of Brazilian English learners within the proficiency levels A2 and B2 and whether the nature of inappropriate representation is affected by the equivalents in L1. The preposition “of” has been selected as the object of analysis because it is highly frequent in English language corpora (CHODOROW et. al., 2010; DAVIES, 2008; LEECH et. al., 2001). As the corpus for this research, the BraSEL Corpus (Brazilian Spoken of English Learners Corpus) is divided by the learners’ proficiency level according to the Common European Framework of Reference for Languages (CEFR). The major finding was that, even though some errors occurred, the use of the preposition “of'” tended to be well-entrenched in the interviewed Brazilian learners’ grammar. Through this result, we may conclude that “of” and its semantic meanings are stable and acquired since the earlier stages of the learning process.